The clock gene Per2 influences the glutamatergic system and modulates alcohol consumption - Spanagel, Rainer; Pendyala, Gurudutt; Abarca, Carolina; Zghoul, Tarek; Sanchis-Segura, Carla; Magnone, Maria Chiara; Lascorz, Jesús; Depner, Martin; Holzberg, David; Soyka, Michael; Schreiber, Stefan; Matsuda, Fumihiko; et al. (Nature medicine, 2005)
Period (Per) genes are involved in regulation of the circadian clock and are thought to modulate several brain functions. We demonstrate that Per2Brdm1 mutant mice, which have a deletion in the PAS domain of the Per2 protein, show alterations in the glutamatergic system. Lowered expression of the glutamate transporter Eaat1 is observed in these animals, leading to reduced uptake of glutamate by astrocytes. As a consequence, glutamate levels increase in the extracellular space of Per2Brdm1 mutant mouse brains. This is accompanied by increased alcohol intake in these animals. In humans, variations of the PER2 gene are associated with regulation of alcohol consumption. Acamprosate, a drug used to prevent craving and relapse in alcoholic patients is thought to act by dampening a hyper-glutamatergic state. This drug reduced augmented glutamate levels and normalized increased alcohol consumption in Per2Brdm1 mutant mice. Collectively, these data establish glutamate as a link between dysfunction of the circadian clock gene Per2 and enhanced alcohol intake.